Sifat Mekanik Beton Dengan Menambah Bakteri Bacillus Subtilis Untuk Aplikasi Beton Pulih Mandiri - Nevita Elisa; Zulfikar Djauhari; Enno Yuniarto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Concrete is a brittle material and has low tensile strength comparing to other material. When the cracks occur, the quality of concrete will decrease, so the new innovations will be created to cover the weakness of concrete. The innovation is self healing concrete that uses bacteria as a medium that can close the cracks of concrete. This research used 25 ml bacillus subtilis with a concentration of 105 cells/ml as admixture to the concrete mix. The test conducted in this research was compressive and flexural tests carried out at the age of 28 dan 56 days. The test consists of two types of loading namely crushing crack test where the concrete cylinder was loaded until it failed and initial crack test when the concrete cylinder was loaded until first crack appeared. For the case of conducted crushing crack bacterial concrete were able to increase compressive strength of 14.71% and flexural strength of 6.96% compared to those of normal concrete at the age of 56 days. Furthermore, initial crack test conducted at bacterial concrete was able to withstand compressive and flexural loads of 17.15% and 3.17% higher than those of normal concrete. Keywords: concrete, crack, bacillus subtilis, compressive strength, flexural strength